E-Selectin/AAV Gene Therapy Promotes Myogenesis and Skeletal Muscle Recovery in a Mouse Hindlimb Ischemia Model - Antoine J. Ribieras; Yulexi Y. Ortiz; Yan Li; Nga T. Le; Carlos T. Huerta; Francesca A. Voza; Hongwei Shao; Roberto I. Vazquez-Padron; Zhao-Jun Liu; Omaida C. Velazquez (Cardiovascular Therapeutics)
The response to ischemia in peripheral artery disease (PAD) depends on compensatory neovascularization and coordination of tissue regeneration. Identifying novel mechanisms regulating these processes is critical to the development of nonsurgical treatments for PAD. E-selectin is an adhesion molecule that mediates cell recruitment during neovascularization. Therapeutic priming of ischemic limb tissues with intramuscular E-selectin gene therapy promotes angiogenesis and reduces tissue loss in a murine hindlimb gangrene model. In this study, we evaluated the effects of E-selectin gene therapy on skeletal muscle recovery, specifically focusing on exercise performance and myofiber regeneration. C57BL/6J mice were treated with intramuscular E-selectin/adeno-associated virus serotype 2/2 gene therapy (E-sel/AAV) or LacZ/AAV2/2 (LacZ/AAV) as control and then subjected to femoral artery coagulation. Recovery of hindlimb perfusion was assessed by laser Doppler perfusion imaging and muscle function by treadmill exhaustion and grip strength testing. After three postoperative weeks, hindlimb muscle was harvested for immunofluorescence analysis. At all postoperative time points, mice treated with E-sel/AAV had improved hindlimb perfusion and exercise capacity. E-sel/AAV gene therapy also increased the coexpression of MyoD and Ki-67 in skeletal muscle progenitors and the proportion of Myh7+ myofibers. Altogether, our findings demonstrate that in addition to improving reperfusion, intramuscular E-sel/AAV gene therapy enhances the regeneration of ischemic skeletal muscle with a corresponding benefit on exercise performance. These results suggest a potential role for E-sel/AAV gene therapy as a nonsurgical adjunct in patients with life-limiting PAD.